The idiosyncratic impact of an aggregate shock: The distributional consequences of COVID-19 - Michaela Benzeval; Jonathan Burton; Thomas Crossley; Paul Fisher; Annette Jäckle; Hamish Low; Brendan Read (Institute for Fiscal Studies (IFS), 2020)
Using new data from the Understanding Society: COVID 19 survey collected in April 2020, we show how the aggregate shock caused by the pandemic affects individuals across the distribution. The survey collects data from existing members of the Under-standing Society panel survey who have been followed for up to 10 years. Understand-ing society is based on probability samples and the Understanding Society Covid19 Survey is carefully constructed to support valid population inferences. Further the panel allows comparisons with a pre-pandemic baseline. We document how the shock of the pandemic translates into different economic shocks for different types of worker: those with less education and precarious employment face the biggest economic shocks. Some of those affected are able to mitigate the impact of the economic shocks: universal credit protects those in the bottom quintile, for example. We estimate the prevalence of the different measures individuals and households take to mitigate the shocks. We show that the opportunities for mitigation are most limited for those most in need.
Keywords: C83; D31; G51; I31; J31; J63; 330; COVID-19; job loss; inequality; mitigation; financial distress